Object-Oriented Programming and Representation of Objects - Drozdek, Adam (Studies in logic, grammar and rhetoric : the Journal of University of Bialystok, 2015)
In this paper, a lesson is drawn from the way class definitions are provided in object-oriented programming. The distinction is introduced between the visible structure given in a class definition and the hidden structure, and then possible connections are indicated between these two structures and the structure of an entity modeled by the class definition.